Pemberdayaan Ekonomi Kreatif melalui Pemanfaatan Limbah Styrofoam Menjadi Barang Bernilai Ekonomis di Kampung Sentra Pengrajin Mainan Pesawat Terbang - Lukman Harahap; Muhammad Husin Al Fatah; Layyin Mahfiana (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2020)
This study aimed to provide an overview of the sociology-economic conditions of the people in Debegan village of Mojosongo, Surakarta after receiving training on miniature craft and aircraft using styrofoam materials from the IAIN Surakarta Research and Service Institute (LP2M) team. The study was expected to provide access to create economic empowerment for village communities. As previously known, the city of Surakarta is a vocational city promoting the community uniqueness to be managed in the form of social, cultural and economic activities. The method used in this study is Participation Action Research (PAR). Participatory Action Research (PAR) is a research method carried out in a participatory manner among citizens in a lower level community whose spirit is to encourage transformative actions. The findings and results of the study showed that this activity received relatively good enthusiasm from the people of Debegan village, Mojosongo, Surakarta City. The level of attendance and frequency of the attended meeting was always more than 20 out of 30 participants. This shows that the 80% target audience attendance was reached successfully. This activity requires further follow up to the training that has been given, with the hope that the community will not only be skilled in making crafts from Styrofoam waste but also have marketing and network skills.